2020
DOI: 10.1177/2515245920927643
|View full text |Cite
|
Sign up to set email alerts
|

Many Labs 5: Replication of van Dijk, van Kleef, Steinel, and van Beest (2008)

Abstract: As part of the Many Labs 5 project, we ran a replication of van Dijk, van Kleef, Steinel, and van Beest’s (2008) study examining the effect of emotions in negotiations. They reported that when the consequences of rejection were low, subjects offered fewer chips to angry bargaining partners than to happy partners. We ran this replication under three protocols: the protocol used in the Reproducibility Project: Psychology, a revised protocol, and an online protocol. The effect averaged one ninth the size of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 14 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…The two project organizers had primary responsibility for drafting the manuscript, and the other authors contributed to revisions, knowing the outcomes of at most one set of replications during the writing process (depending on which individual studies they helped conduct). The full reports of the individual replication studies are reported separately in this issue (Baranski et al, 2020; Buttrick et al, 2020; Chartier et al, 2020; Corker et al, 2020; Ebersole et al, 2020; IJzerman et al, 2020; Lazarević et al, 2020; Mathur et al, 2020; Rabagliati et al, 2020; Skorb et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two project organizers had primary responsibility for drafting the manuscript, and the other authors contributed to revisions, knowing the outcomes of at most one set of replications during the writing process (depending on which individual studies they helped conduct). The full reports of the individual replication studies are reported separately in this issue (Baranski et al, 2020; Buttrick et al, 2020; Chartier et al, 2020; Corker et al, 2020; Ebersole et al, 2020; IJzerman et al, 2020; Lazarević et al, 2020; Mathur et al, 2020; Rabagliati et al, 2020; Skorb et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…However, because it matches neither the RP:P protocol nor what was recommended during review, it is not included in the analysis here. For more detail, see Skorb et al (2020, this issue).…”
mentioning
confidence: 99%
“…One of the other full successes had participants observe an exchange (a supposedly unscripted social interaction) and tracked their eye movements during it. Two studies used computers but simulated live, ongoing interactions, and these had some findings, albeit weak ones, consistent with the original (Bouwmeester et al, 2017;Skorb et al, 2020). Thus, the few studies featuring genuine interpersonal interaction replicated reasonably well.…”
Section: Explaining Failuresmentioning
confidence: 56%
“…Findings by Moran et al (2021) and Vohs et al (2021) were significant or not depending on how many participants were excluded from analyses. Skorb et al (2020) tried three different protocols, of which only one provided a significant result, and that was after excluding over half the sample. Baranski et al (2020) replicated a finding about imaginary perpetrators but not the complementary finding for imaginary victims-thus contradicting the overarching theoretical point despite replicating one of the findings.…”
Section: Mixed Successesmentioning
confidence: 99%
See 1 more Smart Citation